The Impact On Street Parking At Jalan Alianyang Kota Pontianak - Indigo, Joerka Wednesday; Said, Said; Kadarini, S. Nurlaily; Mukti, Elsa Tri; Sumiyattinah, Sumiyattinah (Jurnal Teknik Sipil, 2022)
The development of activities on Jalan Alianyang, Kota Pontianak causes problems,namely the decrease in mobility on the road. This is due to the unavailability of a separateparking area for each of the facilities mentioned above, so parking is carried out using theroad. This causes a reduction in road capasity and causes a decrease in speed for passingvehicles. The purpose of this study is to determine the condition of parking on JalanAlianyang Pontianak in the form of available parking spaces, and the parkingcharacteristics of vehicle owners, to determine the magnitude of side friction due to onstreet parking, getting a road performance value by considering on street parking. Themethod used is based on MKJI (1997) and the Technical Guidelines of the DirectorateGeneral of Land Transportation (1998). Data collection in this study includes primary dataobtained from survey research in the field which includes geometric data on JalanAlianyang, traffic volume data, vehicle speed data, side friction data, and patrol parkingdata. The secondary data was obtained from the Mayor's Decree on Pontianak City Roadon Parking in Kota Pontianak and data from the Pontianak City Population and CivilRegistration Agency. The study was conducted for 4 days on June 24 to 27, 2022 on theJalan Alianyang segment between Jalan Pangeran Natakusuma and Jalan Suwignyo from06.00 to 21.00 WIB. From the results of the analysis can be concluded that the highestaccumulation of hourly parking on weekdays 45 motorcycles and 30 cars, on weekends40 motorcycles and 12 cars. The largest parking volume on weekdays is 1043 vehicles, onweekends is 780 vehicles. The highest average parking index along 200 m is 80% whichmeans that not all road segments are used as parking lots. The performance of road sectionswithout on street parking shows a level of service C and a degree of saturation of 0.45.Meanwhile, with the influence of on street parking with a level of service F and a degreeof saturation of 1.01. Based on parking needs, it can be considered using one side of theroad with good parking management so that parking and mobility needs can be balanced.